North Atlantic Multi-decadal Variability Simulated in Coupled General Circulation Models (CGCMs) - Ba, Jin (2012)
Atlantic Multi-decadal Variability (AMV) is investigated with a number of Coupled General Circulation Models (CGCMs) in this work. There are two parts to these analyses. One is a multi-model comparison with observations, focusing one of the leading proposed mechanisms; the other is the analysis of the mechanism for AMV in one model in detail. A multi-model analysis of AMV is performed to assess similarities to observation and the robustness of the mechanism proposed by Delworth et al. 1993 (D93) that the salinity-induced density anomalies in the sinking region are transported by the Subpolar Gyre (SPG) drive Atlantic Meridional Overturning Circulation (AMOC). The analysis includes preindustrial control simulations from 14 CGCMs. AMV indices in most of models show enhanced power on multi-decadal time scale, but with different periodicity. Sea Surface Temperature (SST) variations related to AMV occur mainly in the mid-latitude region. Fluctuations in the AMOC tend to precede the mid-latitude SST variations, consistent with them being mainly driven by AMOC changes. The wintertime oceanic deep convection sites and their relation to AMOC variability differ among models. The Kiel Climate Model (KCM) provides the strongest evidence that wintertime oceanic convection drives AMOC fluctuations. Furthermore, KCM is the only model with a similar mechanism to D93. There is only one model in which salinity in the “AMOC driving” sinking region is not related with variations in the SPG. In all other models, except KCM, variations in convection in the sinking region tend to strengthen the SPG and then drive AMOC. The relationship between AMOC and North Atlantic Oscillation (NAO) is not clear in these models, except in one model where NAO variations tend to lead AMOC changes by about 10 years. None of these models has a significant relationship between convection and Sea Level Pressure (SLP). However, analysis of the role of atmospheric variability in AMV requires further investigation and is beyond the scope of this thesis. The ...